2016
DOI: 10.3892/ol.2016.4539
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Ang2-siRNA chitosan magnetic nanoparticles and the effect on Ang2 gene expression in human malignant melanoma cells

Abstract: Abstract. The aim of the present study was to construct angiopoietin-2 (Ang2)-small interfering (si)RNA chitosan magnetic nanoparticles and to observe the interference effects of the nanoparticles on the expression of the Ang2 gene in human malignant melanoma cells. Ang2-siRNA chitosan magnetic nanoparticles were constructed and transfected into human malignant melanoma cells in vitro. Red fluorescent protein expression was observed, and the transfection efficiency was analyzed. Reverse transcription-quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The particles resist the permeability reduction of nanoparticles induced by the increased tumor interstitial pressure when particle size is small, thereby increasing the targeting of nanoparticles ( 26 ). The average particle size of Ang2-siRNA plasmid vector/chitosan magnetic nanoparticles prepared by the present study was 67 nm ( 9 ). Therefore, they were used as a suitable targeting drug delivery system.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The particles resist the permeability reduction of nanoparticles induced by the increased tumor interstitial pressure when particle size is small, thereby increasing the targeting of nanoparticles ( 26 ). The average particle size of Ang2-siRNA plasmid vector/chitosan magnetic nanoparticles prepared by the present study was 67 nm ( 9 ). Therefore, they were used as a suitable targeting drug delivery system.…”
Section: Discussionmentioning
confidence: 85%
“…The formed magnetic nanoparticles would be able to accumulate directly towards the target organs under external magnetic field, thus serving its roles ( 7 , 8 ). Using this technique, our previous in vitro experiments confirmed that angiopoietin 2-small interfering RNA (Ang2-siRNA) chitosan magnetic nanoparticles could inhibit the expression of Ang2 gene in human malignant melanoma (MM) cells, and the inhibition efficiency was 59.56% ( 9 ). In the present study, Ang2-siRNA plasmid/chitosan magnetic nanoparticles were injected into the nude mouse MM model to observe the targeting characteristic of these particles under external magnetic field, in order to determine certain foundations for further in vivo targeting intervention studies investigating the tumor growth in MM-transplanted nude mice.…”
Section: Introductionmentioning
confidence: 94%
“…The Ang2-siRNA plasmid particles were encapsulated by chitosan, which does not increase systemic toxicity and is stable in vivo. 27 Additionally, the combination of the Ang2-siRNA system and the magnetic targeted drug delivery system can improve the function of siRNAs in vivo. Moreover, when the siRNA nucleic acid transfer system is used in combination with the chitosan magnetic nanoparticles, the serum pharmacokinetics of the targeted drug delivery system and the half-life of the composite nanoparticles can prolong the siRNA interference effect, which may result in lasting RNA interference effects and enhance the efficacy of gene interference treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Here we reviewed the strategies to enhance delivery efficiency and efficacy of nanomedicine by focusing on normalization of vasculature and the enhancement of extravasation of nanomedicine into tumors. By presenting insights into the basics of nanomedicine–vasculature interactions in tumors, we hope it would provide novel strategies to engineer cancer nanomedicine to accelerate their translation and fulfill the promises of this field ( Table 2 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ).…”
Section: Novel Therapeutics Towards Tumor Vascular Normalizationmentioning
confidence: 99%
“… Target/strategy Cargo/engineered nanoparticle Ref. Nanomedicine to normalize tumor vasculature Angiogenesis signalling pathway VEGFA-VEGFR2 Knockdown of VEGFA by: siRNA/PLCP 94 siRNA/PEI-SWNTs 95 shRNA/dtACPP-modified PEG-DGL 96 Inhibition of VEGFR2 by: Antibody/MSV 97 Ang2 Knockdown of Ang2 by: siRNA/chitosan magnetic nanoparticles 98 Blockage of Ang2-Tie2 interaction by: T4 peptide (K(DEAP)-AAN-NLLMAAS)/PEG 99 PDGF PDGF/PLGA–pSi-ES 100 Immune-associated cell populations and signalling: TAMs Targeting TAMs-specific ligands by: MTX/FOLR2 conjugated G5-dendrimer 101 HA/Mannose receptor conjugated MnO 2 NPs 102 siVEGF/M2pep conjugated AuNPs 103 Enhance extravasation of nanomedicine into tumor Transcytosis-based delivery Adsorptive-mediated transcytosis (AMT) CPT/PBEAGA zwitterionic polymer 104 Receptor-mediated transcytosis (RMT) Targeting iRGD/integrins α v by: siPLK1 and miR-200c/iRGD conjugated MSN 105 CA4 and DOX/iRGD conjugated MSN 106 Targeting GD16/Dll4 by: PTX/GD16 conjugated aldehyde-PEG-PLA and MPEG-PLA block copolymers 107 Immune cell-based delivery PTX/cationic liposomes (PTX-CL)-NEs to form PTX-CL/NEs …”
Section: Novel Therapeutics Towards Tumor Vascular Normalizationmentioning
confidence: 99%